2017
DOI: 10.3389/fpubh.2017.00280
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Response to ELF-MF and Heat: Evidence for a Common Involvement of Heat Shock Proteins?

Abstract: It has been shown that magnetic fields in the extremely low frequency range (ELF-MF) can act as a stressor in various in vivo or in vitro systems, at flux density levels below those inducing excitation of nerve and muscle cells, which are setting the limits used by most generally accepted exposure guidelines, such as the ones published by the International Commission on Non-Ionizing Radiation Protection. In response to a variety of physiological and environmental factors, including heat, cells activate an anci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 75 publications
1
9
0
1
Order By: Relevance
“…These findings are consistent with recent research highlighting the importance of ROS signaling in the cell in general (13,(17)(18)(19) and in regeneration specifically (20,23,28,29). In addition, these data are consistent with studies that have linked EMF exposure to both increased Hsp70 expression and increased regeneration (30)(31)(32). Previous studies have also shown the importance of ROS signaling in initiating apoptotic-induced compensatory proliferation during regeneration (20).…”
Section: Resultssupporting
confidence: 91%
“…These findings are consistent with recent research highlighting the importance of ROS signaling in the cell in general (13,(17)(18)(19) and in regeneration specifically (20,23,28,29). In addition, these data are consistent with studies that have linked EMF exposure to both increased Hsp70 expression and increased regeneration (30)(31)(32). Previous studies have also shown the importance of ROS signaling in initiating apoptotic-induced compensatory proliferation during regeneration (20).…”
Section: Resultssupporting
confidence: 91%
“…According to some studies (20)(21)(22), a possible mechanism that may describe the difference between high and low magnetic flux densities of 50-Hz -MF on BM cell proliferation is that in higher densities, cells sense 50-Hz MFs as a robust stressor and express stress proteins such as heat shock proteins (HSPs). These proteins act as molecular chaperones and protect the cells from apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…The process results in a subtle heterogeneously distributed thermal effect with the resonant conditions [ 87 , 88 ]. Research shows that the nonthermal resonant absorption adds to HSP expression [ 89 ] and function [ 90 ].…”
Section: Electromagnetic Methods Of Hyperthermia In Oncologymentioning
confidence: 99%